The Predictive Model for Recurrent Diarrhea in Children Aged 12-59 Months at Tanah Kali Kedinding Public Health Center, Surabaya - Alfi Layali Muntaza; Dominicus Husada; Sofia Alfarizi (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Recurrent diarrhea occurs repeatedly within a short period, between one and three months or more than once per year. Diarrhea is a leading cause of toddler deaths globally, including in Indonesia with 100,000 deaths annually. Identifying factors predicting recurrent diarrhea significantly impacts prevention efforts. Objectives: This research aims to create a prediction model for the incidence of recurrent diarrhea in toddlers at the Tanah Kali Kedinding Community Health Center, Surabaya. Methods: This research method was a retrospective observational analytical study with a case-control design, involving 80 toddlers (40 case samples and 40 control samples) selected through purposive sampling. The independent variable was recurrent diarrhea in toddlers. The dependent variables were birth weight, nutritional status, measles immunization status, vitamin A suplementation, breastfeeding patterns, and mother's hand washing habits. The instrument used was a questionnaire. Data analysis used simple and multiple logistic regression. Results: The research showed that the incidence of recurrent diarrhea was related to malnutrition status (p = 0.008, OR = 20.184), measles immunization status (p = 0.029, OR = 9.599), breastfeeding pattern (p = 0.002, OR = 15.270), and maternal hand washing habits (p = 0.001, OR = 15.917). Meanwhile, factors that were not significantly related included birth weight (p = 0.397) and vitamin A suplementation (p = 0.456) Conclusions: Factors that influenced the formation of a prediction model for the incidence of recurrent diarrhea in toddlers were malnutrition status, measles immunization status, breastfeeding patterns, and mother's hand washing habits.